2018
DOI: 10.1039/c8ob01720d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of phosphotriazole 5′ mRNA cap analogues as efficient translation initiators

Abstract: Augmenting the mRNA translation efficiency and stability by replacing the standard 7-methylguanosine 5'-cap with properly designed analogues is a viable strategy for increasing the in vivo expression of proteins from exogenously delivered mRNA. However, the development of novel cap analogues with superior biological properties is hampered by the challenges associated with the synthesis of such highly modified nucleotides. To provide a simpler alternative to traditional methods for cap analogue preparation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…To remove in vitro transcription by-products of unintended size RNA samples were gel-purified using PAA elution buffer (0.3 M sodium acetate, 1 mM EDTA, 0.05% Triton X-100), precipitated with isopropanol and dissolved in water. In order to obtain capped fraction of in vitro transcribed short RNAs, transcripts were treated with 5’-polyphosphatase (Epicentre) and Xrn1 (New England Biolabs) as described previously (33). Finally, to generate homogenous 3’-ends in those short RNAs, the transcripts (1 µM) were incubated with 1 µM DNAzyme 10-23 (TGATCGGCTAGGCTAGCTACAACGAGGCTGGCCGC) in 50 mM MgCl 2 and 50 mM Tris-HCl pH 8.0 for 1 h at 37 °C (32), which allowed to produce 3’-homogenous 25-nt RNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove in vitro transcription by-products of unintended size RNA samples were gel-purified using PAA elution buffer (0.3 M sodium acetate, 1 mM EDTA, 0.05% Triton X-100), precipitated with isopropanol and dissolved in water. In order to obtain capped fraction of in vitro transcribed short RNAs, transcripts were treated with 5’-polyphosphatase (Epicentre) and Xrn1 (New England Biolabs) as described previously (33). Finally, to generate homogenous 3’-ends in those short RNAs, the transcripts (1 µM) were incubated with 1 µM DNAzyme 10-23 (TGATCGGCTAGGCTAGCTACAACGAGGCTGGCCGC) in 50 mM MgCl 2 and 50 mM Tris-HCl pH 8.0 for 1 h at 37 °C (32), which allowed to produce 3’-homogenous 25-nt RNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Quality of transcripts was checked on native 1.2% 1xTBE agarose gel, whereas concentration was determined spectrophotometrically. To remove uncapped RNA, transcripts were treated with 5’-polyphosphatase (Epicentre) and Xrn1 (New England Biolabs) as previously described (33). Finally, to deplete dsRNA by-products of in vitro transcription, mRNAs were purified on Agilent Technologies Series 1200 HPLC using RNASep™ Prep – RNA Purification Column (ADS Biotec) at 55 °C as described in (35).…”
Section: Methodsmentioning
confidence: 99%
“…Walczak and co‐workers reported the chemical synthesis of several phosphotriazole cap analogs in order to study its biochemical properties of binding affinity for eIF4E, susceptibility to hDcp2‐catalyzed decapping and translational efficiency. [38] The copper(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) reaction of phosphonate derivatives of 7,2′‐ O ‐dimethyl gunaosine 74 with 5′‐[P2‐N‐(2‐azidoethyl)diphosphate 75 a or 5′‐[P−O‐(2‐azidoethyl)phosphate 75 b,c in the presence of copper sulphate and sodium ascorbate under aqueous conditions afforded the corresponding dinucleotide cap analog containing a triazole moiety within the phosphate chain 76 (Scheme 9 ). Similarly, the CuAAC reaction of phosphonate derivative of guanosine 77 with 5′‐azido‐5′‐deoxy‐7methylguanosine ( 78 ) furnished the corresponding dinucleotide cap analog containing a triazole moiety directly attached to m 7 G 7 9 (Scheme 10 ).…”
Section: Chemical Synthesis Of Cap Analogsmentioning
confidence: 99%
“…Dinucleotide cap analogs have also been investigated as small molecule inhibitors of cap-dependent translation, which could counteract elevated eIF4E levels in cancer cells [10][11][12][13][14]. Recently, we showed that conjugating dinucleotide cap analogs with transporting vehicles produces cell permeable compounds that induce apoptosis of cancer cells [15].…”
Section: Introductionmentioning
confidence: 99%